Bioaccessibility of BDE 47 in a simulated gastrointestinal system and its metabolic transformation mechanisms in Caco-2 cells. (January 2019) - Chen, Guangchun; Jiang, Xiaofeng; Gu, Chenggang; Sun, Cheng; Li, Mei
Abstract: Polybrominated diphenyl ethers (PBDEs) have been regarded as ubiquitous environmental pollutants. However, the absorption and transformation of these compounds after ingestion are not well understood yet. In this study, the bioaccessibility and metabolic pathway of 2, 2′, 4, 4′- tetrabromodiphenyl ether (BDE47) was investigated in an in vitro digestion/Caco-2 cell. Gastric and intestinal bioaccessibilities of BDE47 in 5 kinds of spiked soil samples were ranging from 11.39 ± 0.83% to 36.02 ± 4.34%, and 48.24 ± 3.24% to 81.52 ± 6.43%, respectively. Upon exposure to differentiated Caco-2 cells for 6 h, it was found that only a small amount of BDE47 in the gastrointestinal (GI) solution could pass through Caco-2 cells, and might enter the body. Moreover, BDE47 was found to be metabolized or transformed into BDE28, BDE75, BDE37, BDE32, BDE15 and BDE8 in Caco-2 cells. The metabolic pathway could be explained by using the Becke three-parameter hybrid functional (B3Lucifer yellow CHP) in the Density Functional Theory (DFT), denoted as the values of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) at the atoms of BDE47 and its metabolic products. The obtained results suggest that oral intake of PBDEs is associated with low bioaccessibility, but also emphasize the risks associated with oral ingestion, namely toxicity resulting from the debromination of highly brominated diphenyl ethers. Although highly brominated diphenyl ethers are known to be the least toxic PBDEs, the debrominated products in human intestinal epithelia may elicit greater than expected toxicity. Highlights: High bioaccessibility and low bioavailability of BDE47 were revealed. BDE47 exposed to Caco-2 cells can be metabolized into BDE28, BDE75, BDE37, BDE32, BDE15 and BDE8. Calculate results of HOMO and LUMO can explain the metabolic pathway of BDE47.